Simple Nonfused‐Ring Electron Acceptors with Noncovalently Conformational Locks for Low‐Cost and High‐Performance Organic Solar Cells Enabled by End‐Group Engineering. (20th October 2021) - Li, Congqi; Zhang, Xin; Yu, Na; Gu, Xiaobin; Qin, Linqing; Wei, Yanan; Liu, Xingzheng; Zhang, Jianqi; Wei, Zhixiang; Tang, Zheng; Shi, Qinqin; Huang, Hui
Abstract: The rapid advance of fused‐ring electron acceptors (FREAs) has greatly promoted the leap‐forward development of organic solar cells (OSCs). However, the synthetic complexity of FREAs may be detrimental for future commercial applications. Recently, nonfused‐ring electron acceptors (NREAs) have been developed to be a promising candidate to maintain a rational balance between cost and performance, of which the cores are composed of simple fused rings (NREAs‐I) or nonfused rings (NREAs‐II). Moreover, "noncovalently conformational locks", are used as an effective strategy to enhance the rigidity and planarity of NREAs and improve device performance. Herein, a novel series of NREAs‐II (PhO4T‐1, PhO4T‐2, and PhO4T‐3) is constructed as a valuable platform for exploring the impact of the end group engineering on optoelectronic properties, intermolecular packing behaviors, and device performance. As a result, a high power conversion efficiency of 13.76% is achieved for PhO4T‐3 based OSCs, which is much higher than those of the PhO4T‐1 and PhO4T‐2‐based devices. Compared with several representative FREAs, PhO4T‐3 possesses the highest figure‐of‐merit value of 133.45 based on a cost‐efficiency evaluation. This work demonstrates that the simple‐structured NREAs‐II are promising candidates for low‐cost and high‐performance OSCs. Abstract : Nonfused‐ring electron acceptors (NREAs) have attracted much attention due to several advantages such as simple synthetic routes, high yields, and low costs. Herein, a series of simple NREAs with S···O noncovalently conformational locks (NoCLs) are constructed. Combining the strategies of NoCLs and end‐group engineering, a record PCE of 13.76% for NREAs‐II based devices was achieved.